Muslim Scholars’ Perception ofn Zakat Management: A Case Study at An Islamic Higher Education - Akbar, Ali (Indonesian Research Journal in Education |IRJE|, 2023)
This research aimed to describe the perception of lecturers at the Faculty of Sharia and Law at the Universitas Islam Negeri Sumatera Utara, Medan, on the management of zakat in Indonesia according to Law Number 23 of 2011. The method used in this research was a descriptive qualitative method by interviewing ten lecturers online  at the Faculty of Sharia and Law at the Universitas Islam Negeri Sumatera Utara, Medan, in 2022/2023. Data were analyzed with a qualitative approach. The results of this research showed that the perception of lecturers at the Faculty of Sharia and Law at the Universitas Islam Negeri Sumatera Utara Medan on the management of zakat in Indonesia, according to Law Number 23 of 2011 was positive. In addition, the positive perception of lecturers at the Faculty of Sharia and Law at the Universitas Islam Negeri Sumatera Utara Medan on the management of zakat in Indonesia according to Law Number 23 of 2011 affected their perceptions of zakat obligation. Implications for policymakers are also discussed.